MODEL OF SMALL HOLDERS DAIRY CATTLE WASTE POLLUTION AT SEVERAL NATURAL PHYSICAL AND ECONOMIC SOCIAL CONDITIONS: A CASE STUDY IN THE PROVINCE OF CENTRAL JAVA - Sarwanto, D; Saeni, Soebarinoto; Alikodra, HS; Sanim, B (ANIMAL PRODUCTION, 2004)
Most of dairy farmings in Indonesia are managed in the forms of smallholder farmings that give more attention to productivity rather than ecological concerns. The purpose of this study was to make models of dairy cattle animal waste pollution on clean water quality and degree of smell at several regions with different natural physical and economic social conditions. This study also investigated the waste management that match with the characteristics, behavior, and the attitude of the farmers in each region.  System approach was used as the method of this study through model simulation with program of Powersim 2.5c. Model compiled based on to component situation of livestock, condition of environment and situation of farmer. Determination of regional sample of sub-province or town until chosen countryside conducted with multistage sampling without randomization (purposive sampling).  Based on the result of research can be concluded that (1) low natural physical region and low economic social condition to have endangering pollution level of environment, (2) the waste management for the region with high natural physical and high economic social of bio gas and composting accompanied by removing to excess of animal waste for regional with low natural physical and low economic social. (Animal Production 6(2): 68-75 (2004) Key Words: model, dairy  cattle, waste pollution